Synthesis and characterization of ZnBTC-based MOFs: effect of solvents and salt - Maria V. Timofeeva; Andrey N. Yankin (Chimica Techno Acta)
In this work, we studied the optimization of synthetic approaches to creating structurally modified metal-organic frameworks under various synthesis conditions. We investigated the influence of the various solvents and zinc salts on the structural characteristics of the metal-organic framework based on benzene-1,3,5-tricarboxylic acid (H3BTC). The results indicate that the variation of the types of both solvent and salt is a parameter affecting the crystallinity, phase purity, and morphology of the metal-organic framework. This was confirmed by comprehensive structural characterization (SEM, EDX, PXRD).